Gender Stereotypes and Self-Efficacy as Determinants of the Glass Ceiling Effect: A Study of Female Civil Servants in Central Java - Firdausia, Salsabila; Yusuf, Munawir; Anggarani, Fadjri Kirana (Jurnal Psikologi, 2020)
Glass ceiling refers to the obstruction of opportunities for female employees to get promoted to higher positions, despite being qualified and having achievements, due to gender discrimination. This study aimed to identify the relationship between gender stereotypes and self-efficacy with the glass ceiling phenomenon experienced by female civil servants in Central Java. Sixty female civil servants were involved as samples. This study used three instruments: glass ceiling scale (Î± = 0.855), gender stereotypes scale (Î± = 0.933), and self-efficacy scale (Î± = 0.879). The data was processed using linear regression analysis. The findings revealed that there was a strong correlation (r = 0.803) between gender stereotypes (Î²1 = 0.377) and self-efficacy (Î²2 = -0.431) with the glass ceiling phenomenon experienced by female civil servants in Central Java.